The Orang Asli and the UNDRIP from rhetoric to recognition - Nicholas, Colin 1955-; Jenita Engi; Teh, Yen Ping (Jaringan Orang Asli Semalaysia, 2010)
This book looks at the application of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) on the First Peoples of Peninsular Malaysia. The UNDRIP ascribes many rights to the Orang Asli as an indigenous people. However, despite Malaysia adopting this declaration, there is an enormous gap between what the UNDRIP aspires for indigenous peoples and what the reality is for the Orang Asli. This book traces the fate of the Orang Asli in history and explains how they came to be in their present situation.